2020
DOI: 10.25259/sni_509_2020
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of superior sagittal sinus with sagittal midline: A surgical application

Abstract: Background: Interhemispheric approach is widely used to surgical management of midline tumors and vascular lesion in and around the third ventricle. Complete exposure of the superior sagittal sinus to obtain adequate working space of midline lesion is difficult, because of the risk to inadvertent injury to the sinus and bridging veins, which may cause several neurological deficits. Understanding the SSS neuroanatomy and its relationships with external surgical landmarks avoid such complications. The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
1
6
1
Order By: Relevance
“…In this study again the author has reported that none of the SSS was found in the midline; almost all had deviations that were again in contrast to the findings of this study. 2…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study again the author has reported that none of the SSS was found in the midline; almost all had deviations that were again in contrast to the findings of this study. 2…”
Section: Discussionmentioning
confidence: 99%
“…3 Oberman et al after measuring the deviation distance of SSS from midline recommended to place the drill or burr holes at a distance of at least 1.7 cm from the midline. 2…”
Section: Surgical Recommendations Based On This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The SSS is a challenging structure to operate around, given the difficulty in controlling an inadvertent laceration [ 6 ]. Oberman et al recently reported that the SSS may be displaced by as far as 16.3 mm in the majority of individuals [ 7 ]. There exists limited literature on surgical approaches to extra-axial pathology around the SSS, with most reports being concerned with the treatment of epidural hematoma.…”
Section: Discussionmentioning
confidence: 99%